A novel biomimetic network amplification strategy designed fluorescent aptasensor based on yolk-shell Fe3O4 nanomaterials for aflatoxin B1 detection. (1st January 2023) - Dong, Xiaoze; Qi, Shuo; Qin, Mingwei; Sun, Yuhan; Lv, Yan; Zhang, Yin; Wang, Zhouping
Highlights: A fluorescent aptasensor for aflatoxin B1 detection via CDNs was proposed. A yolk-shell Fe3 O4 -based nanomaterials Au@Fe3 O4 @Void@N-C is used to modify aptamer as magnetron aptamer probe. A new type of biomimetic network-CDNs can be used as an amplification strategy for detecting analytes. Abstract: In this study, yolk-shell Fe3 O4 -based nanomaterials designing of fluorescent aptasensor using a new type of biomimetic network-constitutional dynamic networks (CDNs) amplification strategy was developed for aflatoxin B1 (AFB1) detection. By ingeniously designing the base sequences A, a, B, b, and coupling with endonuclease ( Bbv CI), a constitutes of CDNs is formed as a fluorescence intensity amplifier. With such design, the as- prepared aptasensor exhibits good sensitivity from 50 fg·mL −1 -50 ng·mL −1 with a detection limit of 35.94 fg·mL −1 . Moreover, the CDNs can achieve 1000-fold amplification in terms of linear range and detection limit. The results confirmed that this new type of biomimetic network amplification strategy can supply-one efficient approach to improve signal amplification. Furthermore, the prepared aptamer sensor was tested for spiked recovery in peanut samples, and the recoveries ranged from 83.79 to 95.06 %, which has confirmed its practical application value in the field of food safety.